PRODUCCIÓN IN VITRO DE BRADIZOÍTOS DE NEOSPORA CANINUM # - Risco Castillo y Cols., Verónica (2019)
Neospora caninum is a parasite identified as a major cause of abortion in cattle and neurological disease in various animal species. It is closely related to Toxoplasma gondii, sharing the ability to persist indefinitely in latent stage within the host as a tissue cyst containing slow-dividing bradyzoites. Here we compared different stress methods to induce in vitro bradyzoite conversion, using MARC-145 cells infected with Nc-Liverpool isolate. The tachyzoite-to-bradyzoite conversion rate was monitored at days 3, 5, and 7 post-stress in a double immunofluorescence assay using a mAb against the tachyzoite antigen SAG1 (aSAG1) and a rabbit serum directed to the intracytoplasmatic bradyzoite antigen BAG1 (aBAG1). Seven-day treatment with sodium nitroprusside 70 µM, offered the highest bradyzoite transformation rate and the best yield of total parasitophorous vacuoles observed. In the present work, we introduce an alternative, simplified and more advantageous method for bradyzoite production of N. caninum, using a reliable cell culture system easy to handle and with promising capacity of parasite purification.